Efektifitas Sistem Pendidikan Dalam Mempengaruhi Terwujudnya Generasi Emas 2045 - Samadhinata, I Made Deva (Metta : Jurnal Ilmu Multidisiplin, 2022)
This study aims to analyze the effectiveness of the education system in influencing the realization of the 2045 golden generation. This research model is descriptive qualitative consisting of library data, data collection is through a selection of books, articles and scientific works. The results of this study are that current education is indeed good enough to help realize the 2045 golden generation, it's just that small improvements are still needed which can later be used to overcome all the negative impacts of the emergence of new technology that continues to change and develop. So we need a Pancasila-based curriculum which can later build students who are obedient to Pancasila values ​​and every subject always contains Pancasila values ​​to suit the basis of our country.